In the last MO question , the following matrix is given: $$M_{ij}=\left[\frac{1+(-1)^{i+j}}{i+j-1}\right]$$ and its inverse has been discussed. Now the problem is further extended to a more general form: $$M'_{ij}=\frac{(z+1)^{i+j-1}-(z -1)^{i+j-1}}{i+j-1}$$ where $-1 \le z \le 1$.

Similarly, is there an explicit formula for the inverse of $M'$? How about if we remove the limitation on $z$ and assume $-\infty \lt z \lt \infty$?


I will consider instead $a(n,z)=\frac{(z+1)^{n+1}-(z-1)^{n+1}}{2(n+1)}$ because then $a(0,z)=1.$

The Hankel determinants $\det\left(a(i+j,z)\right)_{i,j=0}^n=\frac{2^{n^2+n}}{ \prod_{j=1}^n (2j+1)\binom{2j}{j}^2}$ are independent of $z.$

Let now $$p(n,x)=\sum_{k=0}^n (-1)^k \binom{n}{k} x^{n-k} \sum_{j=0}^{\lfloor{\frac{k}{2}}\rfloor}(-1)^j z^{k-2j}\binom{k}{2j} \frac{(2j-1)!!(2n-2j-1)!!}{(2n-1)!!}.$$

The inverse of the Hankel matrix is $$(\left(a(i+j,z)\right)_{i,j=0}^n)^{-1}=\left(b(i,j,z)\right)_{i,j=0}^n,$$ where $b(i,j,z)$ is the coefficient of $x^iy^j$ in $\sum_{k=0}^n \frac{2k+1}{4^k}\binom{2k}{k}^2 p(k,x)p(k,y)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.